Effect of Drain Spacing on Reclamation of Waterlogged Areas - Panigrahi, B; Behera, B P; Samantrai, S K (Journal of Agricultural Engineering, 2007)
A field experiment was carried out at the Regional Research and Technology Transfer Station, Chiplima for 6 consecutive years to study the effect of drain spacing in reclamation of waterlogged areas in loamy soil under shallow water table condition. Three drain spacing of 10, 15 and 20 m and two cropping systems of rice-wheat-mung and rice-mustard-sesamum were laid out for the study. 10 m drain spacing was found to be more effective in regulation of excess water from the field and lowering the groundwater table than the other two. At 10 m spacing, the grain yield of rice was maximum (52.47 q/ha) with highest water-use-efficiency (76.17 kg/ha/cm). The same drain spacing also resulted in highest yield and water-use-efficiency of other dry crops like wheat, mung, mustard and sesamum. 10 m drain spacing not only quickly removed the excess water from the crop field (drainage coefficient is 10.76 x 10?5cm/s) but also gave maximum net return and benefit-cost ratio (Rs. 7350/ha and 1.31, respectively for rice-wheat-mung and Rs. 6637/ha and 1.29, respectively for rice-mustard-sesamum) as compared to other two drain spacing. The lowering of the groundwater table after 6 years ofthe experiment was maximum (30.3 cm) for the 10 m drain spacing whereas it was minimum (24.2 cm for 20 m drain spacing).